Employee Recruitment, Selection, and Placement Processes: A Bibliometric Analysis - Septiana, Hana; Septiana, Aulia (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This study aims to analyze the process of recruitment, selection, and placement of employees in the company. Bibliometric analysis methods are used to measure, analyze, and understand patterns in scientific literature and scientific publications related to employee recruitment, selection, and placement. Through searching using the Publish or Perish tool, 984 articles were obtained selected according to research needs, starting from 2019 to 2023. The results of this study conclude the results that recruitment, selection, and placement of employees affect employee performance. Good and appropriate employee recruitment, selection, and placement processes can be applied to improve employee performance. The theoretical implication of this study lies in its use of bibliometric analysis methods to systematically assess the scientific literature on employee recruitment, selection, and placement. The study offers a comprehensive understanding of patterns and trends in relevant scholarly publications in recruitment and employee placement. The contribution of this research is evident in its conclusion that effective processes in recruitment, selection, and placement significantly impact employee performance, emphasizing the importance of implementing suitable strategies to enhance overall workforce effectiveness.